Frankincense and myrrh and their bioactive compounds ameliorate the multiple myeloma through regulation of metabolome profiling and JAK/STAT signaling pathway based on U266 cells - Rumeng Gao; Xiaodong Miao; Chengjing Sun; Shulan Su; Yue Zhu; Dawei Qian; Zhen Ouyang; Jinao Duan (BMC, 2020)
Abstract Background Frankincense and myrrh are used as traditional anti-inflammatory and analgesic medicines in China. It has been reported that frankincense and myrrh have significant anti-tumor activities. The present study was designed to investigate the inhibitory efficacy of frankincense ethanol extracts (RXC), myrrh ethanol extracts (MYC), frankincense -myrrh ethanol extracts (YDC), frankincense -myrrh water extracts (YDS) and their main compounds on U266 human multiple myeloma cell line. Methods The inhibition effects of cell proliferation was evaluated by MTT assays. Cell culture supernatant was collected for estimation of cytokines. Western blot analysis was designed to investigate the regulatory of JAK/STAT signal pathway. In addition, cell metabolomics based on the ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS) had been established to investigate the holistic efficacy of frankincense and myrrh on U266 cells. Acquired data were processed by partial least-squares discriminant analysis (PLS-DA) and orthogonal projection to latent structures squares-discriminant analysis (OPLS-DA) to identify potential biomarkers. Results RXC, MYC significantly inhibited the proliferation of U266 cells at dose of 25-400 μg/mL, YDC and YDS at the dose of 12.5-400 μg/mL. 3-O-acetyl-α-boswellic acid, 3-acetyl-11 keto-boswellic acid and 11-keto-boswellic acid had the most significant anti- multiple myeloma activities in the 10 compounds investigated, therefore these 3 compounds were selected as representatives for Elisa assay and western blotting experiments. All the extracts and active compounds ameliorated the secretion of cytokines and down-regulated the expression of JAK/STAT signaling pathway-related proteins. Comparing RXC, MYC, YDC and YDS-treated U266 cells with vehicle control (DMSO), 13, 8, 7, 7 distinct metabolites and 2, 2, 3, 0 metabolic target pathways involved in amino acid metabolism, lipid metabolism, vitamin metabolism, arachidonic acid were identified, respectively. Conclusions Taken together our results suggest that the frankincense and myrrh and their bioactive compounds inhibit proliferation of U266 multiple myeloma cells by regulating JAK/STAT signaling pathway and cellular metabolic profile.